Organ at risk delineation for radiation therapy clinical trials: Global Harmonization Group consensus guidelines. (September 2020) - Mir, Romaana; Kelly, Sarah M.; Xiao, Ying; Moore, Alisha; Clark, Catharine H.; Clementel, Enrico; Corning, Coreen; Ebert, Martin; Hoskin, Peter; Hurkmans, Coen W.; Ishikura, Satoshi; Kristensen, Ingrid; et al.
Highlights: The GHG identified an unmet need for standardized OAR contouring guidance. AAPM TG 263 recommendations exist for all but 10 OAR structures. Here we present consensus guidance on 73 OARs with nomenclature and peer-reviewed descriptions. Abstract: Background and purpose: The Global Quality Assurance of Radiation Therapy Clinical Trials Harmonization Group (GHG) is a collaborative group of Radiation Therapy Quality Assurance (RTQA) Groups harmonizing and improving RTQA for multi-institutional clinical trials. The objective of the GHG OAR Working Group was to unify OAR contouring guidance across RTQA groups by compiling a single reference list of OARs in line with AAPM TG 263 and ASTRO, together with peer-reviewed, anatomically defined contouring guidance for integration into clinical trial protocols independent of the radiation therapy delivery technique. Materials and methods: The GHG OAR Working Group comprised of 22 multi-professional members from 6 international RTQA Groups and affiliated organizations conducted the work in 3 stages: (1) Clinical trial documentation review and identification of structures of interest (2) Review of existing contouring guidance and survey of proposed OAR contouring guidance (3) Review of survey feedback with recommendations for contouring guidance with standardized OAR nomenclature. Results: 157 clinical trials were examined; 222 OAR structures were identified. Duplicates, non-anatomical, non-specific, structures with more specific alternative nomenclature, and structures identified by one RTQA group were excluded leaving 58 structures of interest. 6 OAR descriptions were accepted with no amendments, 41 required minor amendments, 6 major amendments, 20 developed as a result of feedback, and 5 structures excluded in response to feedback. The final GHG consensus guidance includes 73 OARs with peer-reviewed descriptions (Appendix A). Conclusion: We provide OAR descriptions with standardized nomenclature for use in clinical trials. A more uniform dataset supports the delivery of clinically relevant and valid conclusions from clinical trials.